Diet and Nutritional Status of the Older Adults in Rural India - Arlappa Nimmathota; Balakrishna Nagalla; Babu Kokku Suresh; Harikumar Rachakula; Mallikharju Rao Kodavanti; Ravindranath Manchala; Kumar Sharad; Ramakrishna KS; Laxmaiah Avula; Brahmam GNV (Journal of Aging Research And Healthcare, 2016)
Objectives: World has witnessed a considerable increase in the proportion of elderly population.Aging is associated with decreased physical activity and metabolism and thereby the changes in the nutritional requirements of older adults.The objective of this communication was to assess the nutritional status of rural elderly population in India. Methodology: A community based cross-sectional study; adopting multistage stratified random sampling procedure was carried out by the National Nutrition Monitoring Bureau (NNMB), during 2005-06 among the rural population of nine major states of India. A total of 3871 older adults were covered for anthropometry and of them, a total of 2138 older adults were covered for dietary assessment. Key Results: In general, the consumption of all the foods was below recommended daily intakes (RDI), and the in-adequacy (<70% of RDI) of intake was high with respect to leafy vegetables, milk & milk products, fats & oils and sugar & jaggery. Similarly, the in-adequacy of intakes of micronutrients such as vitamin A, iron, riboflavin and free folic acid was high among both genders. The poor intake of diet was reflected in high prevalence of chronic energy deficiency (CED) among the rural elderly in India. Conclusions: In general,the rural elderly were subsisting on inadequate diets in terms of both quantity and quality. Similarly, the prevalence of CED among elderly is a ‘‘very high’’ public health nutrition problem in India. Therefore, the Government of India should initiate appropriate nutrition intervention measures to improve the overall nutritional status and special nutrition policies to address the health and nutritional problems of the aging population.
Keywords: Nutritional status